ANALYSIS OF COPYRIGHT AS A FIDUCIARY SECURITY LINKED TO POSITIVE LAW IN INDONESIA AND COMPARISON WITH THE UNITED STATES - Kelvin Adytia Pratama; Dr. Brian Amy Prastyo (Universitas Labuhanbatu, 2024)
Law number 28 of 2014 concerning Copyright stipulates that Copyright as an intangible movable object can be used as an object of fiduciary guarantees. Provisions regarding Copyright as an object of fiduciary security will be implemented in accordance with the provisions of the applicable laws and regulations. However, in reality, this is still being debated by various related parties, especially regarding the mechanism for assessing and binding guarantees, so that until now there has been no party that has provided credit with collateral in the form of a Copyright. This study uses a normative juridical method and aims to study the mechanisms for assessing and binding Copyright as an object of fiduciary guarantees in Indonesia, by comparing it to the method used in Common Law countries namely United States of America.Keywords : Copyright, Fiduciary Guarantee, Creative Economy, Valuation Method, Common Law